2012
DOI: 10.1345/aph.1r128
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Angiotensin-Converting Enzyme Inhibitors and Angiotensin Receptor Blockers on Risk of Atrial Fibrillation before Coronary Artery Bypass Grafting

Abstract: The studies reviewed here had conflicting results. Randomized placebo-controlled trials are necessary to determine the risk for atrial fibrillation after CABG associated with preoperative use of ACE inhibitors and ARBs. The decision to continue or withhold the drugs is not evidence-based and should be based on a patient's other clinical characteristics.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…18, 2729 Studies in adult populations following coronary artery bypass grafting have yielded conflicting results with respect to the utility of preoperative angiotensin converting enzyme inhibition and reduction in the incidence of postoperative atrial fibrillation. 3033 To our knowledge, no series to date has evaluated for a potential association between preoperative ACE inhibition and postoperative tachyarrhythmias in children.…”
Section: Discussionmentioning
confidence: 99%
“…18, 2729 Studies in adult populations following coronary artery bypass grafting have yielded conflicting results with respect to the utility of preoperative angiotensin converting enzyme inhibition and reduction in the incidence of postoperative atrial fibrillation. 3033 To our knowledge, no series to date has evaluated for a potential association between preoperative ACE inhibition and postoperative tachyarrhythmias in children.…”
Section: Discussionmentioning
confidence: 99%
“…However, it has been shown that the angiotensin II type 1 (AT 1 ) receptor antagonist reduced heart rate and QT dispersion in hypertensive patients and the two actions were independent of changes in blood pressure (BP) (3). AT 1 antagonist losartan directly modified the human cardiac repolarizing K + currents (4), which means that the reduction in VAs may not be a consequence of depressurization and hypertrophic changes. The present study tested the hypothesis that the AT 1 receptor antagonist reversed repolarization abnormities of LV myocytes in spontaneously hypertensive (SH) rats which was independent of changes in BP.…”
Section: Introductionmentioning
confidence: 99%
“…Atrial fibrillation (AF) occurs in 20-50% of patients following cardiac surgery [28][29][30][31] , with incidence peaking on the second postoperative day 32 . Postoperative AF leads to prolonged hospital length of stay 33 , higher hospital costs [33][34][35][36] and increased in-hospital and 4-year mortality 37,38 .…”
mentioning
confidence: 99%